2023
DOI: 10.2147/copd.s424128
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Concepts for Triple Therapy Use in Patients with COPD: A Delphi Consensus

Marc Miravitlles,
Sudeep Acharya,
Bhumika Aggarwal
et al.

Abstract: Purpose Role of triple therapy in chronic obstructive pulmonary disease (COPD) management is supported by growing evidence, but consensus is lacking on various aspects. We conducted a Delphi survey in respiratory experts on the effects of triple therapy on exacerbation reduction, early optimization, pneumonia risk, and mortality benefits in COPD management. Methods The study comprised 2-round online surveys and a participant meeting with 21 respiratory experts from 10 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The DEPICT study demonstrated long-term benefits of early initiation of triple therapy at an earlier stage of the disease [ 21 ]. Further, triple therapy also reduces the risks of mortality and exacerbations [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DEPICT study demonstrated long-term benefits of early initiation of triple therapy at an earlier stage of the disease [ 21 ]. Further, triple therapy also reduces the risks of mortality and exacerbations [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Triple therapy should be given to patients with clinical indication, proper vaccination protocol and better control of comorbidities, thus preventing the development of other respiratory infections. Similarly, another Delphi study reported that in addition to ICS use, a patient with COPD was more likely to develop pneumonia if they had a history of smoking, diabetes, pneumonia, or exacerbations; older age, lower BMI, and severe airway obstruction [ 22 ].…”
Section: Discussionmentioning
confidence: 99%